Widow cleansing and inheritance among the Luo in Kenya: the need for additional women‐centred HIV prevention options. Issue 2 (26th June 2014) - Perry, Brian; Oluoch, Lennah; Agot, Kawango; Taylor, Jamilah; Onyango, Jacob; Ouma, Lilian; Otieno, Caroline; Wong, Christina; Corneli, Amy
Abstract : Introduction: The customs of widow cleansing and widow inheritance are practiced in several communities throughout sub‐Saharan Africa. In the Nyanza Province of Kenya, according to tradition, Luo widows are expected to engage in sexual intercourse with a "cleanser, " without the use of a condom, in order to remove the impurity ascribed to her after her husband's death. Luo couples, including widows, are also expected to engage in sex preceding specific agricultural activities, building homes, funerals, weddings, and other significant cultural and social events. Widows who are inherited for the purpose of fulfilling cultural obligation have a higher prevalence of HIV than those who remain un‐inherited or are inherited for the purpose of companionship. Methods: As part of a larger descriptive qualitative study to inform study procedures for FEM‐PrEP, an HIV prevention pre‐exposure prophylaxis clinical trial, we conducted 15 semi‐structured interviews (SSIs) with widows, 15 SSIs with inheritors, and four focus group discussions with widows in the Bondo and Rarieda districts in Nyanza Province to explore the HIV risk context within widow cleansing and inheritance practices. Thematic qualitative analysis was used to analyze the data. Results: The majority of widows reported in the demographic questionnaire being inherited, and most widows in the SSIs described participating in the cleansing ritual. We identified two main themes related to HIV prevention within the context of widow cleansing and inheritance: 1) widows must balance limiting their risk for HIV infection with meeting cultural expectations and ensuring that their livelihood needs are met, and 2) sexual abstinence undermines cultural expectations in widowhood while the use of condoms is deemed inappropriate in fulfilling culturally prescribed sexual rituals, and is often beyond the widow's ability to negotiate. Conclusions: Women‐controlled HIV prevention methods such as antiretroviral‐based oral pre‐exposure prophylaxis, vaginal gels, and vaginal rings are needed for HIV‐negative widows who engage in sexual rituals related to widowhood.